2016
DOI: 10.1038/srep20453
|View full text |Cite
|
Sign up to set email alerts
|

Bif-1 deficiency impairs lipid homeostasis and causes obesity accompanied by insulin resistance

Abstract: Bif-1 is a membrane-curvature inducing protein that is implicated in the regulation of autophagy and tumorigenesis. Here, we report that Bif-1 plays a critical role in regulating lipid catabolism to control the size of lipid droplets and prevent the development of obesity and insulin resistance upon aging or dietary challenge. Our data show that Bif-1 deficiency promotes the expansion of adipose tissue mass without altering food intake or physical activities. While Bif-1 is dispensable for adipose tissue devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Autophagy is an evolutionary conserved catabolic process by which cellular components are engulfed in an autophagosome and delivered to the lysosome for degradation (Kaur and Debnath, ). Autophagy is emerging as a potential regulator of lipid metabolism and obesity (Liu et al ., ), because this process mediates the lipolysis of TAG and reduces the storage of lipids in adipocytes (Singh et al ., ; López‐Vicario et al ., ; Soussi et al ., ). Finally, it is important to mention that in contrast to previous reports by Mitschke et al .…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an evolutionary conserved catabolic process by which cellular components are engulfed in an autophagosome and delivered to the lysosome for degradation (Kaur and Debnath, ). Autophagy is emerging as a potential regulator of lipid metabolism and obesity (Liu et al ., ), because this process mediates the lipolysis of TAG and reduces the storage of lipids in adipocytes (Singh et al ., ; López‐Vicario et al ., ; Soussi et al ., ). Finally, it is important to mention that in contrast to previous reports by Mitschke et al .…”
Section: Discussionmentioning
confidence: 99%
“…These authors demonstrated that an inhibition of lysosomal function in macrophages not only favored increased lipid retention, but also resulted in reduced levels of lipolysis in the WAT. The membrane curvature-sensing protein endophilin B1, known to be highly expressed in human adipose tissue, may also play a key role in obesity: genetic knockouts of endophilin B1 resulted in mice that displayed an enhanced susceptibility to body weight gain compared to control littermates [113]. In contrast to WAT, lipophagy may play a more important role in lipid homeostasis in the metabolically active brown adipose tissue: indeed, Martinez-Lopez et al .…”
Section: Lipophagy In Disease Statesmentioning
confidence: 99%
“…A novel protein recently implicated in the regulation of autophagic lipolysis is the membrane curvature protein Bif-1 [28]. In adipocytes, autophagy induces Bif-1-dependent PLIN1 degradation and Bif-1 deficiency leads to decreased TG hydrolysis, suggesting that PLIN1 degradation is necessary for autophagy-driven LD breakdown.…”
Section: Targeting Lds For Selective Autophagymentioning
confidence: 99%
“…Bif-1 deficiency resulted in adipose tissue hypertrophy, obesity and hyperinsulinemia with high fat diet feeding or aging. However, Bif-1 deficiency did not inhibit adipose tissue lipolysis upon fasting [28], suggesting that lipophagy is not essential to hormone-stimulated adipocyte lipolysis. Cell-type differences may therefore exist in lipophagy, but interpretation of the role of lipophagy in adipose tissue is complicated by effects of autophagy on adipocyte differentiation [29,30], although loss of Bif-1 was reported not to have this effect [28].…”
Section: Targeting Lds For Selective Autophagymentioning
confidence: 99%
See 1 more Smart Citation